2013
DOI: 10.1016/j.joa.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

ST‐segment elevation and ventricular fibrillation shortly after transseptal puncture for left atrial catheter ablation

Abstract: A 47‐year‐old man with drug‐resistant paroxysmal atrial fibrillation underwent left atrial (LA) catheter ablation. After sheaths were inserted into the LA using the Brockenbrough method, he complained of angina and developed ST‐segment elevation in the II, III, aVF, V5, and V6 leads. Ventricular fibrillation (VF) occurred followed by ventricular tachycardia. The VF was successfully treated with direct current shock. Coronary angiography with isosorbide dinitrate showed neither spasm nor embolism in the coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, a Brugada‐like ECG induced by catheter manipulation during ischemic VT ablation has not been previously reported. There are many reports of ST elevation in the inferior leads during ablation after the Brockenbrough technique [3]; however, this patient exhibited an ECG change mainly in leads V1 and V2 without any reciprocal changes within 5 min of the Brockenbrough approach. The mechanism of the ECG change was unknown.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…To the best of our knowledge, a Brugada‐like ECG induced by catheter manipulation during ischemic VT ablation has not been previously reported. There are many reports of ST elevation in the inferior leads during ablation after the Brockenbrough technique [3]; however, this patient exhibited an ECG change mainly in leads V1 and V2 without any reciprocal changes within 5 min of the Brockenbrough approach. The mechanism of the ECG change was unknown.…”
Section: Discussionmentioning
confidence: 63%
“…The conus branch of the right coronary artery is well known to supply the right ventricular outflow tract. Air embolisms and vasospasms during ablation have been reported in several cases [3]. In this case, ischemia of the conus branch of the right coronary artery was considerable; however, the absence of chest symptoms and immediate recovery of ST elevation indicates that involvement of the coved‐type ECG change and ischemia was impossible to verify.…”
Section: Discussionmentioning
confidence: 75%
“…Another study found that the phenomenon of STE occurred mostly after transseptal puncture, even after ablation. 7 There was only one case of a patient who exhibited STE and sinus bradycardia during repeated compression of the fossa ovalis by a sheath catheter, but they resolved soon after atropine administration. 4 This phenomenon is believed to be a short-term one and benign.…”
Section: Discussionmentioning
confidence: 99%
“…The cases of most patients were either self-relieving or their condition resolved in a few minutes with atropine and fast saline drip. 7 …”
Section: Discussionmentioning
confidence: 99%
“…The Bezold-Jarisch reflex is an inhibitory reflex originating from sensory cardiac receptors with vagal afferent fibers that are influenced by chemical or mechanical stimuli. This stimulation increases parasympathetic activity and inhibits sympathetic activity, producing bradycardia, vasodilation and hypotension 5,8,9 . Right coronary dilation, hypotension and bradycardia would result in coronary hypoperfusion and regional and transient myocardial ischemia, which can generate electrocardiographic changes in the ST segment during transseptal puncture 2,5 , however, the hypothesis of the reflex similar to that of Bezold-Jarisch leading to ST change does not explain the fact that, after a few minutes of septal puncture, the clinical and electrocardiographic changes disappear, despite the continuous stimulation of the septum by the presence of the sheath used during the puncture.…”
Section: Discussionmentioning
confidence: 99%